2016
DOI: 10.1039/c6ra02038k
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite/cellulose nanocrystals/silk fibroin ternary scaffolds for rat calvarial defect regeneration

Abstract: The purpose of this study was to design and characterise a novel biomimetic scaffold for the repair of critical size calvarial defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…A similar system based on nanocellulose, hydroxyapatite, and silk fibroin has been proposed for the regeneration of a rat brain/skull defect ( Figure 9 ) [ 118 ]. When investigating the effect of the nanocomposite on MC3T3-F1 cells’ viability, it was found that the cell viability at 5 and 7 days was much higher than that of samples without the composite material.…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar system based on nanocellulose, hydroxyapatite, and silk fibroin has been proposed for the regeneration of a rat brain/skull defect ( Figure 9 ) [ 118 ]. When investigating the effect of the nanocomposite on MC3T3-F1 cells’ viability, it was found that the cell viability at 5 and 7 days was much higher than that of samples without the composite material.…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%
“… Illustration of the different repair results in rat calvarial defects assessed by micro-CT. Reproduced with permission from [ 118 ], 2011, Royal Society of Chemistry. …”
Section: Figurementioning
confidence: 99%
“…Bone defects can result in severe complications such as pain, obvious limitation in daily activities, and sometimes even lead to psychological problems. Tissue engineering scaffold has been rapidly developed as a viable approach to regenerate bone . Implantation of bioactive scaffolds alone or in combination with growth factors into a defect site can recruit host cells for the purpose of inducing osteogenic differentiation of the cells for bone regeneration …”
Section: Introductionmentioning
confidence: 99%
“…Ideal bone biomaterials should have good mechanical properties, excellent biocompatibility, and should be degraded at moderate rates to be consistent with bone regeneration, which are crucial for the repair of bone defects. Furthermore, good osteoconductivity, even osteoinductivity, and high porosity with interconnecting structures were also highly demanded . Many inorganic materials have been applied to prepare bone tissue engineering scaffolds such as nanohydroxyapatite (nHAp), β-tricalcium phosphate (β-TCP), and bioactive glass.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] Among natural biopolymer materials, natural proteins isolated from animal tissues or animal plasmas are widely studied for constructing tissue engineering scaffolds, due to their excellent biocompatibility, biodegradability, absorbability, and available approaches of isolation from the varied sources. [17][18][19][20] Proteins are generally fabricated into porous scaffolds by first cross-linking reaction and then freeze-drying technique. The cross-linking reaction is employed to improve the mechanical stability of protein scaffolds.…”
Section: Introductionmentioning
confidence: 99%